2004
DOI: 10.1111/j.1365-3091.2004.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

C and O stable isotope variability in recent freshwater carbonates (River Krka, Croatia)

Abstract: Three types of recent carbonate precipitates from the River Krka, Croatia, were analysed: (1) bulk tufa from four main cascades in a 34 km long section of the river flow through the Krka National Park; (2) a laminar stromatolite-like incrustation formed in the tunnel of a hydroelectric power plant close to the lowest cascade; and (3) recent precipitates collected on artificial substrates during winter, spring and summer periods. Stable isotope compositions of carbon (d 13 C) and oxygen (d 18 O) in the carbonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 54 publications
3
57
0
2
Order By: Relevance
“…Despite the absence of a major river, we interpret the strongly negative oxygen values as expression of freshwater influx by springs or rivulets, lowering the elevated isotope level of the lake water. Modern rivers in the area have isotopically rather heavy d 18 O values of c. -8% and d 13 C DIC values of c. -12 to -13% (Lojen et al, 2004). These data fit excellently to the observed freshwater end-member data in the mollusc aragonite.…”
Section: Stable Isotope Composition Of the Palaeolakessupporting
confidence: 62%
“…Despite the absence of a major river, we interpret the strongly negative oxygen values as expression of freshwater influx by springs or rivulets, lowering the elevated isotope level of the lake water. Modern rivers in the area have isotopically rather heavy d 18 O values of c. -8% and d 13 C DIC values of c. -12 to -13% (Lojen et al, 2004). These data fit excellently to the observed freshwater end-member data in the mollusc aragonite.…”
Section: Stable Isotope Composition Of the Palaeolakessupporting
confidence: 62%
“…As many studies have shown, isotopic equilibrium is rarely maintained under natural conditions during calcite precipitation (Gonfiantini et al, 1968;Friedman, 1970;Fouke et al, 2000;Lojen et al, 2004Lojen et al, , 2009Kele et al, 2008Kele et al, , 2011. In earth surface travertine depositing environments the situation is even more complex due to the intense CO 2 outgassing and high precipitation rates.…”
Section: Non-equilibrium Oxygen Isotope Fractionation At Upstream Sitmentioning
confidence: 96%
“…Therefore, coupled hydrochemical and sedimentological analyses are crucial to decipher the factors that control the variations in the tufa deposition's attributes through space and time. Moreover, the stable-isotope composition of the water and related sediment can record short-term climatic and hydrological changes on different time scales (i.e., seasonal, interannual and decadal); thus this type of analysis is useful to infer highresolution environmental changes (Lojen et al, 2004;Andrews, 2006;Osácar et al, 2013a, b).…”
Section: Introductionmentioning
confidence: 98%